THERAPEUTIC DRUG MONITORING OF LAMOTRIGINE: DEVELOPMENT OF PHARMACOKINETIC APPROACHES AIMING AT THE INDIVIDUAL-BASED ANTICONVULSIVE PHARMACOTHERAPY - D. A. Abaimov; A. K. Sariev; M. V. Tankevich; E. Yu. Styrova; V. V. Schvedkov; T. Yu. Noskova; R. D. Seifulla (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: this paper presents the results of therapeutic drug monitoring of lamotrigine, an anticonvulsant epilepsy medication, in patients with cryptogenic focal epilepsy using plasma and saliva as a biological material for drug testing. Comparative analysis of the steady-state plasma and saliva lamotrigine concentrations (СssMIN and СssMAX) allows the conclusion that saliva can be used as a suitable biological substrate for therapeutic drug monitoring.